PENGARUH BEBAN KERJA, STRES KERJA, MOTIVASI DAN KEPUASAN KERJA TERHADAP KINERJA ANGGOTA SATUAN KERJA DIT RESKRIMUM POLDA SULAWESI TENGGARA - Evi Afrianto; Buyung Sarita; Asrip Putera (Jurnal Manajemen, Bisnis dan Organisasi (JUMBO), 2022)
This study aims to: 1) determine the effect of workload, work stress, motivation and job satisfaction simultaneously on the performance of members of the Directorate of Criminal Investigation at the Southeast Sulawesi Regional Police, 2) determine the effect of workload on the performance of members of the Directorate of Criminal Investigation at the Regional Police of Southeast Sulawesi, 3) knowing that work stress affects the performance of members of the Directorate of Criminal Investigation at the Southeast Sulawesi Regional Police, 4) knowing that motivation affects the performance of members of the Directorate of Criminal Investigation at the Regional Police of Southeast Sulawesi, and 5) knowing the effect of job satisfaction on the performance of members of the Directorate of Criminal Investigation at the Regional Police of Southeast Sulawesi.The object of this research is the Directorate of Criminal Investigation of the Southeast Sulawesi Regional Police. The population of the study was police officers who served in the Directorate of Criminal Investigation at the Southeast Sulawesi Regional Police, totaling 112 personnel. Determination of the sample using the Slovin formula with a precision of 10% percent thus the research sample amounted to 53 respondents. Collecting research data using questionnaires, research data were analyzed using SPSS ver 22 to determine the results of regression analysis of the influence of the independent variable on the dependent variableThe results of the study: 1) Workload has a positive and significant effect on the performance of members of the Directorate of Criminal Investigation at the Regional Police of Southeast Sulawesi, 2) Job stress has a positive and significant effect on the performance of members of the Directorate of Criminal Investigation at the Regional Police of Southeast Sulawesi, 3) Motivation has a positive and significant effect on the performance of members of the Directorate of Criminal Investigation at the Regional Police. Southeast Sulawesi, 4) Job satisfaction has a positive and significant effect on the performance of members of the Directorate of Criminal Investigation at the Regional Police of Southeast Sulawesi, 5) Simultaneous and positive effects of workload, work stress, work motivation and job satisfaction on the performance of members of the Directorate of Criminal Investigation at the Regional Police of Southeast Sulawesi.